Catecholaminergic Polymorphic Ventricular Tachycardia in a Patient With Recurrent Exertional Syncope - Kim, Na Young; Kang, Jung Kyu; Park, Sun Hee; Bae, Myung Hwan; Lee, Jang Hoon; Yang, Dong Heon; Park, Hun Sik; Chae, Shung Chull; Jun, Jae Eun; Cho, Yongkeun (Korean circulation journal, 2012)
A 16-year-old male with a prior history of recurrent syncope was referred to our hospital after being resuscitated from cardiac arrest developed while playing volleyball. His electrocardiogram (ECG) demonstrated ventricular fibrillation at a local emergency department. After referral, an ECG showed bidirectional ventricular tachycardia (VT) and nonsustained Torsade de Pointes. Two days later, his heart rate became regular, and no additional episodes of VT were observed. His ECG showed sinus rhythm with a corrected QT interval of 423 msec, and two-dimensional echocardiography was unremarkable. We made the diagnosis of a catecholaminergic polymorphic VT. However, only premature ventricular complex bigeminy was induced on exercise ECG and epinephrine infusion tests, and the patient showed no episodes of syncope. His father and mother had different missense mutations in the cardiac ryanodine receptor on genetic testing. The proband had both mutations in different alleles and was symptomatic. It was recommended that the patient avoid competitive physical activities, and a β-blocker was prescribed.